A justiça restaurativa como via de acesso à justiça - Caio Augusto Souza Lara (2013)
The dissertation now presented is the study of restorative justice as a methodology able to promote access to justice, both in the sense of access to the courts, such as the access to a just legal order in a multiport system that draws in the Brazilian judicial system after the Resolution nº 125 of the National Council of Justice. Based on the analysis of the constitutive elements of the paradigm of justice presented, this work aimed to demonstrate how the justice current system, mainly concerned with the punishment to be imposed on the offender and not always meet the expectations of those who felt this transgression can and to what extent, be complemented by restorative system that is not only concerned with the repair material damage but also with moral reparation and relationships in search of a peaceful future and promoting culture of peace. Sought to unravel the origins of the model, detect how the international movement restorative influenced our society and if it comes reflecting effectively into a significant leap in the quality of treatment of conflict resolution. It was sought to investigate and assess the trend of the use of restorative practices and their compatibility with the national legal system, establishing an overview of the application of new ideas in Brazil, so that they were demonstrated the conditions for development of the new paradigm. Therefore, was adopted the type of methodological research legal-projective. Lastly, we sought to illustrate the research paper with the study of particularities of the brazilian programs and projects of Restorative Justice.